Detectorists. Series 2 [videorecording (DVD)] - Crook, Mackenzie, 1971-; Stirling, Rachael, 1977-; Jones, Toby, 1966-; Quigley, Pearce (Acorn, 2016)
Andy is still out of a job and struggling to provide for his wife, Becky, and new son. Lance is still unlucky in love, though someone special unexpectedly walks into his life.